2016
DOI: 10.1586/1744666x.2016.1147956
|View full text |Cite
|
Sign up to set email alerts
|

Chemokine and chemokine receptors in autoimmunity: the case of primary biliary cholangitis

Abstract: Summary Chemokines represent a major mediator of innate immunity and play a key role in the selective recruitment of cells during localized inflammatory responses. Beyond critical extracellular mediators of leukocyte trafficking, chemokines and their cognate receptors are expressed by a variety of resident and infiltrating cells (monocytes, lymphocytes, NK cells, mast cells, and NKT cells). Chemokines represent ideal candidates for mechanistic studies (particularly in murine models) to better understand the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 159 publications
0
40
0
Order By: Relevance
“…Thence we compared the expression of chemokine receptors on MDSCs in IgG4-SC and HCs. We demonstrated that the expression of CCR2, CCR5, CCR6, CXCR3, and CX3CR1 (30)(31)(32)(33) on MDSCs was significantly increased in IgG4-SC compared to HCs (Fig. 3D; Supporting Fig.…”
Section: Rankl Induces Mdsc Expansion and Expression Of Ccr5 Cxcr3 mentioning
confidence: 87%
“…Thence we compared the expression of chemokine receptors on MDSCs in IgG4-SC and HCs. We demonstrated that the expression of CCR2, CCR5, CCR6, CXCR3, and CX3CR1 (30)(31)(32)(33) on MDSCs was significantly increased in IgG4-SC compared to HCs (Fig. 3D; Supporting Fig.…”
Section: Rankl Induces Mdsc Expansion and Expression Of Ccr5 Cxcr3 mentioning
confidence: 87%
“…The interaction of CX 3 CL1 and its receptor CX 3 CR1 contributes to the recruitment of various immune cells including T cells, monocytes and NK cells causing inflammatory autoimmune diseases such as RA and SLE. [96][97][98][99] Moreover, stimulation by CX 3 CL1 was found to trigger the proliferation of fibroblasts and atherosclerosis as well as leading to an increased MMPs and further inflammation in RA joints. [100][101][102][103][104] Multiple studies in RA have been carried out with antagonists and/or neutralizing antibodies against chemokines including CCR1, CCR5, CXCR4, CXCR7, CCL19, CXCL10, CXCL12, and CXCL13, where they revealed potential to be future targets.…”
Section: Chemokines In Rheumatoid Arthritismentioning
confidence: 99%
“…Recently, obeticholic acid, a selective ligand of the farnesoid X receptor, was approved for patients who are refractory to UDCA . However, the efficacy of obeticholic acid is still suboptimal, and additional therapeutic approaches are urgently needed …”
Section: Introductionmentioning
confidence: 99%